Femmes et négociations diplomatiques entre France et Espagne au xviiie siècle - Guillaume Hanotin (Genre & Histoire)
In the courtly world, women were often present and thus indirectly contributed to the exercise of power in the entourage of a prince. The study of women's networks of an ambassador to the court of Madrid in the early eighteenth century provides an opportunity to highlight how they could intervene in the conduct of negotiations. The example of the ambassador Amelot de Gournay helps to clarify the relationship of women's networks with those which were more specifically male. In the secrecy of diplomatic correspondence, the presence of women is rarely detected. However, the relative silence of the sources is not a sign of women’s absence in diplomacy. Within the plural network of a negotiator that mingled "friends", relatives and allies, sources reveal the role (specific?) reserved for women. This article paper aims to outline their participation, and the uniqueness of their place and their work in diplomatic missions.